The use of aromatherapy in clinical and interprofessional practice (Research, Society and Development, 2021)
Aromatherapy makes use of essential oils through topical, inhalation or olfactory application, aiming at the prevention, cure and reduction of symptoms, being one of the oldest complementary practices in the world, being recognized and used in many countries, both in the treatment of health problems as well as promoting well-being and quality of life. This article aims to identify the functions of aromatherapy in health care by drawing an overview of how it is configured, in national and international literature, with regard to the use of aromatherapy as a tool for reducing anxiety and promoting psychological well-being. and the contribution to interprofessional work. It is a literature review, where from the search for articles in the Medline and Scielo databases, published between 2009 and 2018 and selected using the descriptors "anxiety" and "aromatherapy", 18 articles were selected for the study. In this way, it is believed that this study contributed in the scope of professional practice, academic training and in the scientific area, as through it, it was possible to identify the effectiveness in the use of some emerging practices nowadays, highlighting the need to rethink the implementation of both teaching models such as extension and research, in addition to assistance.